Merger of Private Universities: Empirical Study STAI Become FAI of Muhammadiyah University Bandung - Sitti Chadidjah; Muhamad Tisna Nugraha; Qiqi Yulianti Zaqiah; Supiana Supiana (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The number of private universities in Indonesia is more than universities in the most populous country in the world, but it is not accompanied by good quality. This research is an empirical study with a descriptive, qualitative research approach. Technical data collection through documents, and observations of the process of unification of STAI and Muhammadiyah University. The unification of these two institutions is in one foundation, namely Muhammadiyah. In this merger process, the Ministry of Education and Culture and the Ministry of Religion are involved. The Chairperson of the Association of Indonesian Private Universities strongly supports the merging of two or more universities to reduce the number, facilitate coaching, and improve the quality of higher education. The first merger process was carried out by the Ministry of Education and Culture after the filing and visitation procedures were completed in writing and the visit of the LLDIKTI chairman followed by submission to DIKTIS (Directorate of Islamic Higher Education). This article aims to prove empirically about the implementation of the Ministry of Education and Culture's policies and the Decree of the Directorate of Islamic Higher Education regarding the merger of two or more universities, 2) information that the merging process of PTKAI and PTU is not easy.